(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the learning interest of fifth-grade students at SD 2 Tenggeles towards subjects presented through data visualization using pictograms. The background emphasizes the importance of understanding students’ learning interests, which directly affect their academic outcomes. The method employed is descriptive qualitative, with data collection through observations, interviews, and questionnaires specifically designed to measure students’ learning interests. The data analysis technique in this study involves processing and interpreting the results of interviews, observations, and documentation qualitatively to evaluate the learning interest of fifth-grade students at SD N 2 Tenggeles regarding subjects presented through pictograms. The research results show that most students have a good interest in the subjects being taught. Pictograms as a medium for presenting data have proven effective in attracting students’ attention and increasing their engagement in the learning process. The indicators measured include feelings of happiness, interest, and student engagement during learning. From the data analysis, it was found that the supporting factors for learning interest include motivation from teachers, a conducive learning environment, and the use of engaging learning media such as pictograms. Conversely, the inhibiting factors include a lack of parental attention and an unsupportive classroom condition.